Fabrication and high temperature electrical conductivity of polymer-derived SiHfBCN ceramic coating - Xichao Dong; Qinghua Zhao; Yao Li; Shaomin Gu; Xinming Xu; Dianwei He; Fang Ye; Laifei Cheng; Xingang Luan; Zhaoju Yu (Journal of Advanced Ceramics)
Wireless surface acoustic wave (SAW) sensors hold great promise for in-situ, real-time monitoring and accurately assessing the health status of hot-end components. However, the thin-film electrode as the SAW sensor core unit with excellent high-temperature conductivity, stability, and oxidation resistance is still a challenge, especially in harsh ultra-high-temperature environments. In this study, we employed a polymer-derived ceramic approach to fabricate smooth and dense SiHfBCN ceramic coatings on YCa4O(BO3)3/BN substrate. The composition, microstructural evolution, and room-temperature and high-temperature electrical conductivity of SiHfBCN ceramic coatings were investigated to reveal the mechanism for controlling electrical conductivity. The results indicate that the electrical conductivity of the SiHfBCN ceramic coating pyrolyzed at a lower temperature of 1200 °C reaches an impressive high value of 291.55 S·m−¹ at 1200 °C in argon. Importantly, the results also demonstrate that the coating has remarkable high-temperature conductivity and excellent repeatability and durability. Therefore, the typical semiconducting behavior of SiHfBCN ceramic coatings highlights their potential as thin-film electrodes for SAW high-temperature sensors in high-temperature extreme environments.